The Fear of Missing Out (FOMO) and Islamic Consumer Ethics: Examining Gen Z Behavior Through A Sharia and Moral Lens - Ahmad Maulidizen; Johari Johari; Maghfirah Maghfirah; Aulia Puspita Roosiani; Muhammad Zailani Iman; Habiburrahman Rizapoor (Madania: Jurnal Kajian Keislaman, 2024)
The Fear of Missing Out (FOMO) phenomenon has increasingly shaped the consumption patterns of Generation Z, driven by the pressure to stay connected and keep up with social trends. This study explores the moral implications of FOMO through the lens of Islamic consumer ethics, which emphasizes principles such as moderation, self-discipline, and ethical responsibility in consumption. The purpose of this research is to investigate how Islamic ethical values can address the FOMO-driven behaviors prevalent in Generation Z, aiming to foster a more balanced and responsible approach to consumption. Using a library research method, the study analyzes various scholarly sources and Islamic teachings, particularly the Quran and Hadith, focusing on key ethical concepts such as Israf, Qana’ah, and Ihtiyat. The findings indicate that the FOMO mindset often leads Generation Z to engage in impulsive consumption and material excess, which contradicts the Islamic principles of moderation and mindfulness in spending. Islamic consumer ethics, with its emphasis on contentment and self-restraint, provides a moral framework that can counter these tendencies by encouraging thoughtful and ethical consumption. The research recommends the implementation of educational programs and awareness campaigns to promote Islamic ethical values, particularly among Generation Z, to mitigate the psychological and financial pressures of FOMO. These efforts can help guide this generation towards a more sustainable, mindful, and ethically conscious lifestyle that aligns with Islamic teachings on consumption. Fenomena Fear of Missing Out (FOMO) semakin memengaruhi pola konsumsi Generasi Z, didorong oleh tekanan untuk tetap terhubung dan mengikuti tren sosial. Penelitian ini membahas implikasi moral dari FOMO melalui perspektif etika konsumen Islam, yang menekankan prinsip moderasi, pengendalian diri, dan tanggung jawab etis dalam konsumsi. Tujuan penelitian ini adalah untuk mengkaji bagaimana nilai-nilai etika Islam dapat mengatasi perilaku konsumsi yang dipengaruhi oleh FOMO di kalangan Generasi Z, dengan harapan menciptakan pendekatan konsumsi yang lebih seimbang dan bertanggung jawab. Dengan menggunakan metode penelitian kepustakaan, studi ini menganalisis berbagai sumber ilmiah dan ajaran Islam, khususnya Al-Qur'an dan Hadis, dengan fokus pada konsep etika utama seperti Israf, Qana’ah, dan Ihtiyat. Hasil penelitian menunjukkan bahwa pola pikir FOMO sering mendorong Generasi Z untuk melakukan konsumsi impulsif dan berlebihan, yang bertentangan dengan prinsip moderasi dan kesadaran dalam pengeluaran menurut Islam. Etika konsumen Islam, dengan penekanannya pada rasa cukup dan pengendalian diri, menawarkan kerangka moral yang dapat mengatasi kecenderungan ini dengan mendorong konsumsi yang lebih bijak dan etis. Penelitian ini merekomendasikan pelaksanaan program edukasi dan kampanye kesadaran untuk mempromosikan nilai-nilai etika Islam, khususnya di kalangan Generasi Z, guna mengurangi tekanan psikologis dan finansial akibat FOMO. Upaya tersebut diharapkan dapat membimbing generasi ini menuju gaya hidup yang lebih berkelanjutan, penuh kesadaran, dan selaras dengan ajaran Islam tentang konsumsi.